Basal cell carcinoma in a patient at two rare sites: a case report - Jain, Prachi; Kalla, Amrit Raj; Kumari, Manisha; Singhvi, Arpita; Joshi, Yogi Raj (International Journal of Research in Medical Sciences, 2025)
Basal cell carcinoma (BCC) is a locally aggressive cutaneous tumor frequently linked to aberrations in the Hedgehog signaling pathway. It typically occurs on sun-exposed areas; however, rare presentations in non-sun-exposed sites have been documented. A 61‐year‐old female presented with a five-year history of a non-healing ulcer on the right leg. Initially misdiagnosed as Lupus vulgaris, repeated biopsies revealed features consistent with infiltrative BCC and, subsequently, a morpheaform subtype with squamous differentiation. In addition, metastasis was noted in the inguinal region. Radiological studies and histopathological evaluations confirmed the diagnosis. This case underscores that BCC may present at atypical, non-sun-exposed sites and can demonstrate local aggressive behavior with regional metastasis. Early recognition and prompt surgical management are essential to prevent further local invasion and metastasis.